2020
DOI: 10.3390/ijerph17062007
|View full text |Cite
|
Sign up to set email alerts
|

Level of Pollution on Surrounding Environment from Landfill Aftercare

Abstract: This work examines how the pollution from landfill aftercare effect the surrounding area and water basins. The subject of the study was a closed landfill where waste was disposed of without any accounting and operation of the landfill. During the study, soil, surface water, and sediment samples were taken over a two-year period. The data obtained compared with the maximum allowable concentrations established in the Northern part of Lithuania. The water sampling sites were selected taking into account the direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The high concentrations of MTE found in the uncontrolled open landfill site have several origins. The high levels of Zn, Sb, and Pb are the consequence of the presence of leachate, which contains many mineral contaminants (Baziene et al 2020). Authors made the same observations confirming that the leachate is highly polluted by MTE, with major contamination by Zn and Pb (Koné et al 2007;Mehdi et al 2007;Sangaré et al 2016).…”
Section: Discussionmentioning
confidence: 86%
“…The high concentrations of MTE found in the uncontrolled open landfill site have several origins. The high levels of Zn, Sb, and Pb are the consequence of the presence of leachate, which contains many mineral contaminants (Baziene et al 2020). Authors made the same observations confirming that the leachate is highly polluted by MTE, with major contamination by Zn and Pb (Koné et al 2007;Mehdi et al 2007;Sangaré et al 2016).…”
Section: Discussionmentioning
confidence: 86%
“…Zhang et al [11] employed the TOUGHREACT software to simulate arsenic migration in geological carbon storage formations proximal to carbon dioxide injection wells, revealing that an elevated gas injection rate enhances metal migration. Furthermore, previous studies have demonstrated that the infiltration of rainwater poses a risk of heavy metal migration in the soil, with the extent of migration being directly proportional to rainfall intensity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The imbalance between waste production and treatment capacity is intensifying the predicament of garbage siege. On the other hand, due to historical factors, there are many non-sanitary landfills in China, and the irregular waste disposal from these landfills has caused severe pollution threats to soil and groundwater [4,5], as well as the risk on surrounding public health [6].…”
Section: Introductionmentioning
confidence: 99%